The Influence of Brand Image and Store Atmosphere on The Purchase Decision of Muslim Consumers - Sudirman, Nur Mutmainnah; Jumarni; Muis, Musrini (LP2M IAIN Palopo, 2025)
This study analyzes the influence of brand image and store atmosphere on Muslim consumers' purchasing decisions at Toko Surya Indah, which operates in the midst of fierce competition with today's modern retail chains. In this context, understanding how these two factors can affect consumer behavior is crucial. This study uses a quantitative method with sampling conducted through random sampling, providing equal opportunities to every member of the population that has been determined through the Lemeshow formula, namely Muslim consumers of Toko Surya Indah.The results of the study show that both the brand image and the atmosphere of the store have a significant influence on the purchase decision of Muslim consumers. These influences are seen both individually and simultaneously, indicating that the two factors complement each other in influencing consumer behavior.